2015
DOI: 10.1016/j.scitotenv.2015.04.108
|View full text |Cite
|
Sign up to set email alerts
|

Modelling atmospheric oxidation of 2-aminoethanol (MEA) emitted from post-combustion capture using WRF–Chem

Abstract: Limiting global warming to less than 2 °C relative to pre-industrial levels would require substantial cuts in anthropogenic emissions of greenhouse gases (IPCC, 2014). Carbon capture and storage (CCS) is an important mitigation technology for reducing anthropogenic carbon dioxide (CO 2 ) emissions from industrial and energy-related point sources. In this process, CO 2 is captured, conditioned, compressed and transported to a storage location for long-term isolation from the atmosphere. Several problems can occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 58 publications
(96 reference statements)
0
23
0
Order By: Relevance
“…In urban environments, UFPs dominate the total PN concentrations, but only make a small contribution to particulate matter. A simplified parameterization for the treatment of the dry deposition and coagulation of particles (Karl et al, 2016) has already been implemented in EPISODE for modelling PN concentrations in Oslo (Kukkonen et al, 2016). The MAFOR aerosol dynamics solver (Karl et al, 2011(Karl et al, , 2016 will be implemented in EPISODE-CityChem to compute information on the size distribution of UFPs and the total PN.…”
Section: Ultrafine Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…In urban environments, UFPs dominate the total PN concentrations, but only make a small contribution to particulate matter. A simplified parameterization for the treatment of the dry deposition and coagulation of particles (Karl et al, 2016) has already been implemented in EPISODE for modelling PN concentrations in Oslo (Kukkonen et al, 2016). The MAFOR aerosol dynamics solver (Karl et al, 2011(Karl et al, , 2016 will be implemented in EPISODE-CityChem to compute information on the size distribution of UFPs and the total PN.…”
Section: Ultrafine Particlesmentioning
confidence: 99%
“…A simplified parameterization for the treatment of the dry deposition and coagulation of particles (Karl et al, 2016) has already been implemented in EPISODE for modelling PN concentrations in Oslo (Kukkonen et al, 2016). The MAFOR aerosol dynamics solver (Karl et al, 2011(Karl et al, , 2016 will be implemented in EPISODE-CityChem to compute information on the size distribution of UFPs and the total PN. The solver includes nucleation, coagulation, growth due to the condensation of sulfuric acid, and low volatile and/or semi-volatile organic vapours from biogenic and anthropogenic sources.…”
Section: Ultrafine Particlesmentioning
confidence: 99%
“…However, direct measurements of the photochemical production of HNCO have only been made in laboratory studies from isolated precursors such as 2-aminoethanol [Borduas et al, 2013]. While modeled HNCO production from 2-aminoethanol oxidation only accounted for 14% of ambient measured HNCO in one study [Karl et al, 2015], ambient mixing ratios of formamide, can account for almost all observed HNCO in some rural environments [Roberts et al, 2014;Sarkar et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…In the 0th carbonation, the generated precipitates were almost SEC, which indicates that Reaction (4) was dominantly carried out, and the chemical reaction time was 4.8 min. However, the reaction time for Equation (8) obtained from the carbonation under the same condition with the pure water could be estimated to be about 12 min. 27 Therefore, the reaction rate of Equation 8 In addition, ethanol and water are not consumed and generated by the reaction in Equation (8).…”
mentioning
confidence: 99%
“…However, the reaction time for Equation (8) obtained from the carbonation under the same condition with the pure water could be estimated to be about 12 min. 27 Therefore, the reaction rate of Equation 8 In addition, ethanol and water are not consumed and generated by the reaction in Equation (8). Therefore, if there is a certain point at which Equation (8) solely occurs during re-carbonation, ECF will remain constant from that point on.…”
mentioning
confidence: 99%